FEATURES OF HORMONAL RESPONSE TO ATYPICAL POWER LOAD IN ATHLETES AND UNTRAINED YOUTHS - Chernozub, A. (World of Medicine and Biology, 2013)
In the work otobrazhenы эksperymentalnыh the results of research about A Features Changes urovnja hormones cortisol and testosterone in the blood and atletov netrenyrovannыh yunoshey in response to ostruyu nestandartnuyu sylovuyu load. Established , that nestandartnoy Using sylovoy load, otlychayuscheysya Peak yntensyvnostyu neznachytelnom obъёme at work here most frequently USED IN athleticism , povыshaet Level yssleduemыh hormones in the blood in the process prodolzhytelnыh busy athleticism is not frozen here urovnja trenirovannosti yunoshey . However , the results pervychnoho control of hormonal response to predlozhennuyu load , demonstryruyut sufficiently suschestvennoe Reduction CONTENT cortisol and testosterone in the blood and so kak atletov netrenyrovannыh yunoshey . Been identified , in turn , that no such suspension character hormonal response to ostruyu sylovuyu load , fyksyrovannoho on protyazhenyy Trejo busy months athleticism , morfometrycheskye INDICATORS sylovыe and abilities of participants obeyh organism groups demonstryruyut polozhytelnuyu dynamics of growth.
Keywords: hormonal reply; nestandartnыe sylovыe load; cortisol; testosterone; trenyrovochnыy process; sylovыe opportunities